2023
DOI: 10.1371/journal.pgen.1010716
|View full text |Cite
|
Sign up to set email alerts
|

Germline stem cell integrity and quiescence are controlled by an AMPK-dependent neuronal trafficking pathway

Abstract: During periods of energetic stress, Caenorhabditis elegans can execute a developmentally quiescent stage called “dauer”, during which all germline stem cells undergo a G2 cell cycle arrest. In animals that lack AMP-activated protein kinase (AMPK) signalling, the germ cells fail to arrest, undergo uncontrolled proliferation, and lose their reproductive capacity upon recovery from this quiescent stage. These germline defects are accompanied by, and likely result from, an altered chromatin landscape and gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…We recently showed that the compromise of the RabGAP tbc-7 suppresses the germline hyperplasia and post-dauer sterility of AMPK mutants (Wong et al, 2023). To determine if the relationship between the partial Rde phenotype and the post-dauer sterility observed in AMPK mutants are linked, we compared the RNAi sensitivity of aak(0) animals with that of aak(0); tbc-7 mutants that exhibit a restoration of post-dauer fertility.…”
Section: Ampk Signalling Regulates Small Rna Homeostasis As Animals E...mentioning
confidence: 99%
See 2 more Smart Citations
“…We recently showed that the compromise of the RabGAP tbc-7 suppresses the germline hyperplasia and post-dauer sterility of AMPK mutants (Wong et al, 2023). To determine if the relationship between the partial Rde phenotype and the post-dauer sterility observed in AMPK mutants are linked, we compared the RNAi sensitivity of aak(0) animals with that of aak(0); tbc-7 mutants that exhibit a restoration of post-dauer fertility.…”
Section: Ampk Signalling Regulates Small Rna Homeostasis As Animals E...mentioning
confidence: 99%
“…These results confirm that the defects caused by loss of AMPK signalling can be corrected by shifting resources to the miRNA biogenesis pathway at the onset of the dauer stage. Increasing the levels of a single pre-miRNA can have a global impact on the miRNA expression landscape; variations in rescue penetrance can then be attributed to the identity of the individual miRNA expressed and to the specific regulatory role it may hold (Wong et al, 2023).…”
Section: A Subset Of Somatic Mirnas Produced Downstream Of Ampk Promo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The AMP-activated protein kinase (AMPK) and its upstream activator, the LKB1 tumor-suppressor orthologue par-4, are essential to establish this quiescence. Not surprisingly, mutants that lack all AMPK signalling are completely sterile following recovery from this stage (2,3).…”
Section: Main Text: Introductionmentioning
confidence: 99%
“…As animals enter the dauer stage, neuronally-expressed AMPK targets a RabGAP protein to ensure that the conserved GTPase RAB-7 remains GTP-bound (3). RAB-7 is essential for early-to-late endosome maturation and the generation of exosomes (4)(5)(6).…”
Section: Main Text: Introductionmentioning
confidence: 99%